Increased Nuchal Translucency and Pregnancy Outcome - A Tahmasebpour; N Baradaran Rafiee; S Ghaffari; A Jamal (Tehran University of Medical Sciences, 2012)
Background: To study the outcome of cases with nuchal translucency (NT) ≥ 95th centile in the first trimester of pregnancy. Methods: This cross sectional study was performed at Iranian Fetal Medicine Foundation (FMF) between January 2009 and December 2011. Totally, 186 cases with NT≥ 95th centile who attended for the first trimester screening were studied. All cases with increased NT including those with normal karyotype were followed up with anomaly scan at 18-22 weeks and fetal echocardiography at 22-24 weeks. Pregnancy outcome was extracted from delivery records and pediatrics notes and telephone interviews. Results: Of screened cases, 186 fetuses had an NT≥95th centile, of them 19.8% were abnormal karyotype, including 29 cases of trisomy 21, three of trisomy 18, two of trisomy 13, three of Turner syndrome. 77.8% did not show any abnormalities on follow-up examinations. 4.6% of cases were found to have malformation antenatally and 4% cases postnatally. 11.4% women elected termination of pregnancy without further follow up. There were 4.6% fetal loss and  1.3% hydrops fetalis. Conclusion: In this unselected population, the study showed one out of four fetuses with enlarged NT had an adverse pregnancy outcome (miscarriage, fetal loss, and fetal abnormalities), however the chance of having a normal child after exclusion of chromosomal abnormalities and adverse pregnancy outcome was 95%.